Exceptions to the binding force of a debtor’s arbitration agreement on the Insolvency Practitioner: Case note on Peace River Hydro Partners v. Petrowest Corp., 2022 SCC 41* - Reinhard, Bork (European Insolvency and Restructuring Journal, 2023)
In this decision, the Canadian Supreme Court had to decide whether an insolvency administrator is bound by an arbitration agreement entered into by the insolvency debtor prior to the commencement of insolvency proceedings and, therefore, whether civil proceedings incompatible with this arbitration agreement must be stayed before the state courts. The court affirms the binding nature of arbitration in principle, but allows an exception in the event that the reference to arbitration would be incompatible with the conduct of proper and efficient insolvency proceedings